Optimization of CV Jogja Telor's Supply Chain Management with Food Supply Chain Network (FSCN) Approach - Tambunan, Greyuni Grace; Tanjung, Dahri; Warcito, Warcito (Jurnal Logistik Indonesia, 2025)
Chicken eggs are an important commodity in Indonesian agribusiness and have the potential to improve the nutrition of the community and the rural economy. CV Jogja Telor is a chicken egg marketing business that is experiencing a production deficit. The qualitative analysis method using FSCN consists of six supply chain elements, namely objectives, structure, management, business processes, and resources. Supply chain performance is analysed quantitatively to assess supply chain efficiency using marketing margins and farmers˜ shares. The research findings indicate that the most efficient marketing channel is channel 1, with a farmers’ share of 100% and a marketing efficiency rate of 28,00%, namely: partner farmers â†’ CV Jogja Telor â†’ bakery. The least efficient marketing channel is marketing channel 4, with a farmer's share of 66,67% and a marketing margin of 33,33%, namely partner farmers â†’ CV Jogja Telor â†’ modern retail â†’ end consumers. Marketing efficiency is aimed at increasing sales to bakeries and reducing the proportion of sales to modern retail, as well as using CV Jogja Telor's branded packaging for modern retail.